EVALUASI PENGENDALIAN INTERN PADA SIKLUS PENGGAJIAN DAN KEPEGAWAIAN UNTUK MENENTUKAN RISIKO FRAUD (Studi Kasus PT World Yamatex Spinning Mills) - Elizabeth Tiur Manurung; Fidelis Apriani (Bina Ekonomi, 2012)
Issues relating to salary or wages, would be detrimental to employees and companies. One reason is the person who did fraud. Adequate internal control is believed to prevent the occurrence of fraud in the company. Two points examined in this study, whether in PT Yamatex Spinning Mills has had adequate internal controls and the relationship between internal control that has been owned by the risk of fraud, especially on the payroll and personnel cycle. The results showed that PT Yamatex Spinning Mills have internal control. This adequate internal control reduces the risk of fraud. Weaknesses that still exist in the company's internal control is the lack of job rotation policy periodically. Authorization policy in the company that is an offset for these weaknesses. The author suggested that the company established a rotation policy positions on a regular basis to prevent someone from being a position for too long and have the opportunity to conduct fraud.Keywords : Internal control, payroll and personnel,fraud